2005
DOI: 10.1177/030802260506800903
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Coordination Disorder and Self-Esteem: Do Occupational Therapy Groups Have a Positive Effect?

Abstract: Children with developmental coordination disorder (DCD) have motor difficulties that impede the acquisition of both functional and academic skills and evidence suggests that these children may also have reduced self-esteem. One approach to treatment often adopted by occupational therapists is in the form of group therapy. Anecdotal evidence indicates that although these groups may produce little improvement in motor skills, there may be an associated increase in the children's self-confidence and self-esteem. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 17 publications
(20 reference statements)
0
19
0
Order By: Relevance
“…2003; Dunford et al . 2005; McWilliams 2005), likely because of a sense of failure in mastering everyday activities (Mandich et al . 2003).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2003; Dunford et al . 2005; McWilliams 2005), likely because of a sense of failure in mastering everyday activities (Mandich et al . 2003).…”
Section: Resultsmentioning
confidence: 99%
“…The more liberal cut‐off for DCD was also employed in several studies without a control group where QOL‐related concerns were identified (Smyth & Anderson 2000; Dunford et al . 2005; McWilliams 2005; Green et al . 2006; Missiuna et al .…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary data have certainly suggested that teacher and parental intervention may help some children with DCD. 29 Standardised questionnaires could be used, such as the Perceived Efficacy and Goal Setting System tool which includes a care giver and teacher questionnaire. 30 31 A child's right to express its views is enshrined in the United Nations Convention on the Rights of the Child, 32 and attempts are being made by clinicians to include the views of the child with coordination difficulties.…”
Section: Further Assessmentmentioning
confidence: 99%
“…There was also an attempt at achieving full census within a borough (Slack and Webber 2007). Variable levels of reflection on research processes were evident (partial exceptions where there were higher levels included Godfrey 2004;McWilliams 2005;Welch and Dawson 2006;McKay et al 2011). Data were typically viewed in realist terms, and, despite some interest in reflective practice in social care, there appeared to be limited awareness of, and engagement with, reflexivity.…”
Section: Introductionmentioning
confidence: 99%
“…There were studies where chosen scales were adopted because their reliability and validity had been established in previous studies (Holmes 1998;Goodacre and Turner 2005;Knox and Menzies 2005;McWilliams 2005). Many studies emphasised the importance of piloting prior to data collection proper (e.g.…”
Section: Introductionmentioning
confidence: 99%